Predicting how color and shape combine in the human visual system to direct attention - Buetti, Simona (Sci Rep, 2019)
Objects in a scene can be distinct from one another along a multitude of visual attributes, such as color and shape, and the more distinct an object is from its surroundings, the easier it is to find it. However, exactly how this distinctiveness advantage arises in vision is not well understood. Here we studied whether and how visual distinctiveness along different visual attributes (color and shape, assessed in four experiments) combine to determine an object’s overall distinctiveness in a scene. Unidimensional distinctiveness scores were used to predict performance in six separate experiments where a target object differed from distractor objects along both color and shape. Results showed that there is mathematical law determining overall distinctiveness as the simple sum of the distinctiveness scores along each visual attribute. Thus, the brain must compute distinctiveness scores independently for each visual attribute before summing them into the overall score that directs human attention.